The Margarico family political elite of Janiuay, Iloilo, Philippines - Cabarles, Helen Agarrado (University of the Philippines in the Visayas, 2005)
This is a descriptive study of the Magarico as a political elite in Janiuay. The study was conducted using interview guide questions for key informants and archival research in gathering pertinent data. The research aims to (1) to identify the reasons that propels the Margarico family to seek political power in the municipal politics of Janiuay; and , (2) to identify the factors that enable the Magaricos to capture political power., The study found out that societal responsibility and public service are their prime reasons in seeking for political power in the municipal politics and that the socio-economic background of the political family is not the prime factor in their access to political positions. There are other factors that cannot account like good public reputation and good tract of records as public servant.